SCADA and its Application in Power Generation and Distribution System - Apar Agrawal; Aprajita; Abhinav Saxena (Journal of Electronic Design Engineering, 2019)
The essential common sources like Coal, gas, Diesel, nuclear and so forth. Is single time useable due to which the quantity of these sources is decreasing day by day. The emission of these fuels is also responsible for air pollution. On the other hand, if we can use renewable sources like hydro power, solar power and wind power to generate electricity such that SCADA system can incorporate to have better monitoring and reliability of the system for proper distribution of load optimise. So we have developed a system in which consumers are connected to different types of power plants via a Grid. The network load and plants are checked and controlled by the SCADA framework. This provides the uninterrupted power supply to the distributors with more reliable solution.